Plasma electrochemistry: development of a reference electrode material for high temperature plasma. - Fowowe, T; Hadzifejzovic, E; Hu, J; Foord, J; Caruana, D (2012)
This report describes the development of a high temperature reference electrode material for gas phase electrochemistry investigations. The electrode is constructed by careful assessment of different metal/metal oxide materials and operational stability in flame electrolyte medium. This will enable reliable dynamic electrochemistry investigations into redox reactions at the solid/gas interface, free of any solvent defined potential window restrictions.